Heathland Restoration Techniques: Ecological Consequences for Plant-Soil and Plant-Animal Interactions. (10th November 2011) - Diaz, Anita; Green, Iain; Evans, Damian
Abstract : We compare the soil and plant community development during heathland restoration on improved farmland when achieved through soil stripping with that achieved through soil acidification. We also test the potential for toxic metals to be made more available to plant and animal species as a result of these treatments. Acidification with elemental sulphur was found to be more effective than soil stripping for establishing an ericaceous sward despite the high levels of phosphate still present within the soil. However, both soil acidification and soil stripping were found to have the potential to increase the availability of potentially toxic metals. Acidification increased uptake of both aluminium and zinc in two common plant species Agrostis capillaris and Rumex acetosella and decreased the abundance of surface active spiders. The potential consequences for composition of restored heathland communities and for functioning of food chains are discussed.